Experimental Study on Surface Roughness and Flank Wear in Turning of Nimonic C263 under Dry Cutting Conditions. (12th October 2021) - Francis Xavier, J.; Ravi, B.; Jayabalakrishnan, D.; Ezilarasan, Chakaravarthy; Jayaseelan, V.; Elias, G.
Abstract : Aircraft component manufacturing sector is looking for high precision machining in aircraft components. The present work explores the operability of green manufacturing of Nimonic C263 using dry turning. Nimonic C263 is tough to turn owing to its inherent quality like low conductivity and more work hardening. Therefore, in order to improve this machined surface/integrity, the controlling factors were optimized based on desirability approach for minimum of surface roughness and flank wear during turning of this alloy using CBN insert. L27 orthogonal array was chosen to carry out the experiment. The effects of controlling factors, such as cutting speed (V ), feed rate (S ), and cut penetration/depth of cut (a p ) on the outputs, were also explored. The feed rate was a major impact to affect surface finish and flank wear. The average error percentage between the experimental and RSM models for surface finish was 4.76 percent and 2.79 percent for flank wear.